Work in Sweden 1974–2010: Work-life inequality at the intersection of class and gender (Sociologisk Forskning, 2017)
This article traces work-life evolution in Sweden during recent decades against the backdrop of long-run structural change tied to class and gender. We examine the development of four key labor market features: (a) occupational sex segregation, (b) gender gaps in job quality, (c) skill upgrading and mismatch, and (d) youth employment. While occupational and educational upgrading is beneficial for most people, some groups face waning work-life prospects. Maintaining social inclusion is the great challenge for the future.